2020
DOI: 10.13057/biodiv/d211245
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Leptospirosis control based on eco-social factors: Modeling combination in Demak, Central Java, Indonesia

Abstract: Abstract. Djati RRAP, Kusnoputanto H, Utomo SW, Sakundarno M, Dewabrata PW, Duad HAH, Wicaksono MA. 2020. Short Communication: Leptospirosis control based on eco-social factors: Modeling combination in Demak, Central Java, Indonesia. Biodiversitas 21: 5818-5828. Ecological habitats and niches of leptospirosis as one of the environmental-based diseases need to be explored in an in-depth study based on eco-social analysis. The objective of this study was to develop an integrated leptospirosis control model based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Our study also reported that the farmers connected more rats with the reduction of predators such as owls. Owl breeding can be an effective way of controlling rodents, as has been shown in other parts of Indonesia [30].…”
Section: Discussionmentioning
confidence: 80%
“…Our study also reported that the farmers connected more rats with the reduction of predators such as owls. Owl breeding can be an effective way of controlling rodents, as has been shown in other parts of Indonesia [30].…”
Section: Discussionmentioning
confidence: 80%
“…The last zoonotic disease that is a priority is leptospirosis, which is transmitted through rodents. High climate change, poor sanitation, and flooding in several regions of Indonesia have great potential for causing this disease [ 20 , 21 ]. These six priority diseases are included in the Regulation of the Coordinating Minister for Human Development and Culture of the Republic of Indonesia Number 7 of 2022, concerning Guidelines for the Prevention and Control of New Zoonoses and Infectious Diseases [ 22 ].…”
Section: Introductionmentioning
confidence: 99%